Possible ways to reduce the cost of grinding process of products with intermittent circles - O. Yakimov; G. Zadorozhko; L. Bovnegra; S. Beznos; V. Balan (Trudy Odesskogo Politehničeskogo Universiteta, 2018)
Grinding in most cases is the final operation of machining, on which the quality of the surface layer of the manu-factured part is formed. Stable quality of the surface layer during grinding and high productivity can be ensured by using grinding wheels with a discontinuous working surface. The purpose of research is to identify the ways to reduce the cost of manufacturing intermittent grind-ing wheels. The results of the studies are applied in engineering methods for calculating the structural elements of interrupted abrasive wheels. Theoretical studies were carried out on the basis of the theory of metal cutting, the theory of oscillations. The cost of grinding in circles with a discontinuous working surface depends to a large extent on the shape and dimensions of the geometric elements that make up the working surface of the abrasive tool and the working conditions of the circles. The main ways of reducing the cost of grinding with pre-sprouted circles are revealed. Engineeringmethods based on the results of conducted research are used at the Lutsk Automobile Plant.